2012
DOI: 10.1063/1.4754602
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier dynamics and interactions in electric force microscopy

Abstract: In electric force microscopy, a charged atomic force microscope tip in vacuum senses a fluctuating electrical force generated by the sample. Such measurements can in principle probe electrical noise generated by moving charge carriers in an organic semiconductor. We present a theory of cantilever frequency fluctuations in electric force microscopy, driven by coupled charge carrier dynamics and dielectric fluctuations. The connection between observable frequency fluctuations in electric force microscopy and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…30 These experiments were motivated by our previously reported scanning probe microscopy study of light-and time-dependent conductivity in a thin film of CsPbBr 3 . 35 We used sample-induced dissipation [36][37][38][39][40][41][42][43][44][45][46][47][48][49] and broadband local dielectric spectroscopy (BLDS) 50 to demonstrate for CsPbBr 3 that conductivity shows a slow activated recovery when the light was switched off, with an activation energy and time-scale consistent with ion motion. We concluded that the sample conductivity dynamics were controlled by the coupled motion of slow and fast charges.…”
Section: Introductionmentioning
confidence: 99%
“…30 These experiments were motivated by our previously reported scanning probe microscopy study of light-and time-dependent conductivity in a thin film of CsPbBr 3 . 35 We used sample-induced dissipation [36][37][38][39][40][41][42][43][44][45][46][47][48][49] and broadband local dielectric spectroscopy (BLDS) 50 to demonstrate for CsPbBr 3 that conductivity shows a slow activated recovery when the light was switched off, with an activation energy and time-scale consistent with ion motion. We concluded that the sample conductivity dynamics were controlled by the coupled motion of slow and fast charges.…”
Section: Introductionmentioning
confidence: 99%
“…3. The solid lines show the pre- dicted heating rate calculated from the measured resistance R m using equations ( 1), (2). The measured data show good agreement with the calculated curves with an average deviation ∆ = 2.06 for T = 97 K and ∆ = 2.12 for T = 140 K. For T < T c , the heating rate spectrum is measured at three different temperatures T = (12, 41, 77) K (Fig.…”
mentioning
confidence: 60%
“…Electric field noise provides insights into microscopic processes, and imposes limitations to experimental systems. In particular, electric field noise in close proximity to surfaces creates obstacles for near-field measurements [1,2], experiments with nitrogen-vacancy centers [3], Casimir effect studies [4], gravitational-wave detectors [5], and ion trapping experiments [6]. It has been suggested to employ the high sensitivity of trapped ions to electric field noise as a new tool in surface science [7].…”
mentioning
confidence: 99%
“…11 was affixed to the leading edge of a fragile microcantilever; it took weeks of scanning to locate the virus via its magnetic resonance signal. 1 The creation of high-compliance microcantilevers with integrated nanomagnet tips [17][18][19] creates exciting opportunities for measuring charge and spin fluctuations in patterned thin-film devices [20][21][22][23][24][25] and observing magnetic resonance in both devices and optically labeled, flash-frozen biological samples [26]. To realize these opportunities in a magnetic resonance force microscope (MRFM), we must first position the cantilever over a chosen micrometer-scale feature on a centimeter-scale sample substrate.…”
Section: Introductionmentioning
confidence: 99%